2002
DOI: 10.1136/bmj.325.7359.301
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of cervicovaginal fetal fibronectin test in predicting risk of spontaneous preterm birth: systematic review

Abstract: Objective To determine the accuracy with which a cervicovaginal fetal fibronectin test predicts spontaneous preterm birth in women with or without symptoms of preterm labour. Design Systematic quantitative review of studies of test accuracy. Data sources Medline, Embase, PASCAL, Biosis, Cochrane Library, Medion, National Research Register, SCISEARCH, conference papers, manual searching of bibliographies of known primary and review articles, and contact with experts and manufacturer. Study selection Two reviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
210
1
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(219 citation statements)
references
References 73 publications
4
210
1
4
Order By: Relevance
“…The alternative to sonographic measurement of cervical length in predicting the outcome of women presenting in threatened preterm labor is biochemical assessment for the presence of fetal fibronectin in cervicovaginal secretions 11 . A recent systematic review of 40 studies on fetal fibronectin in women presenting with threatened preterm labor reported that the likelihood ratio for positive results for predicting delivery within 7-10 days of presentation was 5.42 (95% CI 4.36-6.74) and the ratio for negative results was 0.25 (95% CI 0.20-0.31) 12 . In a multicenter study involving 763 women presenting with threatened preterm labor, fetal fibronectin was positive in 20% of women.…”
Section: Discussionmentioning
confidence: 99%
“…The alternative to sonographic measurement of cervical length in predicting the outcome of women presenting in threatened preterm labor is biochemical assessment for the presence of fetal fibronectin in cervicovaginal secretions 11 . A recent systematic review of 40 studies on fetal fibronectin in women presenting with threatened preterm labor reported that the likelihood ratio for positive results for predicting delivery within 7-10 days of presentation was 5.42 (95% CI 4.36-6.74) and the ratio for negative results was 0.25 (95% CI 0.20-0.31) 12 . In a multicenter study involving 763 women presenting with threatened preterm labor, fetal fibronectin was positive in 20% of women.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these results, fFN yielded a sensitivity of 66.7%, specificity of 87.9%, PPV of 36.4% and NPV of 96.2% (Table 3), comparable with other published data. 5,13,14 Women presenting with symptoms of PTL with cervical change (>3 cm dilation, Group 3) were not tested with the QuikCheck TM fFN kit. Utilising the same 64 women in whom albumin and VDBP were both assayed, a comparison of the efficacy of fFN with a combined biomarker model (albumin and VDBP) for the prediction of labour within 7 days was made.…”
Section: Comparison Of Candidate Biomarkers With Ffn For the Predictimentioning
confidence: 99%
“…These tests, however, have limited application in identifying women who will deliver preterm, because of their relatively low sensitivity and poor positive predictive values (PPVs). 5,6 In contrast, their utility relies on their high negative predictive value (NPV) in recognising women who are unlikely to deliver preterm.…”
Section: Introductionmentioning
confidence: 99%
“…For these women, there is a need to identify those who will go on to deliver prematurely because the key clinical decisions following testing relate to immediate management and outcome. For example, if cervicovaginal fetal fibronectin testing could predict spontaneous preterm birth among these women before advanced cervical dilatation, 23 then antenatal maternal intramuscular corticosteroid injection may be administered to accelerate fetal lung maturity to prevent respiratory distress syndrome. 24 In utero transfer to a tertiary intensive neonatal care unit able to care for the premature neonate may also be considered.…”
Section: Delineation Of the Problemmentioning
confidence: 99%